Gambaran Tingkat Kecemasan Ibu Hamil Pada Trimester III di Wilayah Kerja Puskesmas Banda Sakti - Iskandar Albin; Maulana Ikhsan; Muhammad Adryan Koto (Jurnal Ilmiah Manusia Dan Kesehatan, 2022)
Pregnancy is a physiological process that occurs and experienced by women. During pregnancy there can be various psychological changes, anxiety is a common psychiatric condition and often occurs in pregnancy, especially during third trimester. The purpose of this study is to find out the anxiety level of pregnant women in third trimester at The Banda Sakti Health Center Work Area. The method used is descriptive research with cross sectional study approach. The sample in this study was 106 pregnant women. The sampling technique used is consecutive sampling. The results: majority of respondents were aged 20-35 years as many 74 people (69,8%), had high school as many 44 people (41,5%), unemployed as many as 82 people (77,4%), and majority of gestational age respondents were 28 weeks (43,4%). A total of 36 people (34%) experienced moderate anxiety, mild anxiety as many 31 people (29,2%), severe anxiety as many 16 people (15,1%), did not experience anxiety as many 23 people (21,7%). Based on status of gravida, multigravida as many 64 people (60,4%), primigravida as many 35 people (33%), and grandemultigravida as many 7 people (6,6%). Conclusion: the majority of multigravida pregnant women experience moderate anxiety with high school education level/equivalent, unemployed and gestational age were 28 weeks.